Lifestyle factors predisposing to cervical dysplasia in women attended in the hospital María Auxiliadora, 2013-2017: Factores del estilo de vida predisponentes a displasia cervical en mujeres atendidas en el hospital María Auxiliadora, 2013-2017 - Gallegos Toribio, Rocío (2019)
Introduction: The cervical clearance is the precursor lesion of cancer of the cervix, in which alterations of the cervical cells are observed. Objective: To identify the predisposing factors for the cervical dispute in the patients treated at the María Auxiliadora Hospital during 2013 to 2017. Methods: Design study, cases, controls, analytical and observational. 216 clinical records of patients will be analyzed, divided into 72 cases and 144 controls. Results: In the bivariate analysis, significant results in early menarche (OR = 2.071, p = 0.024), the early sexual intercourse (OR = 2.213, p = 0.017), having multiple sexual partners (OR = 3.036; = 0.001) and multiparity (OR = 2.316, p = 0.005). In the multivariate analysis, the independent variables were multiple sexual partners (OR = 2.626, p = 0.003) and multiparity (OR = 2.759, p = 0.045). Conclusion: It is concluded that women with multiple sexual partners and with multiparity are at higher risk to develop cervical dysplasia. DOI:10.25176/RFMH.v19.n2.2065